2011
DOI: 10.2979/jfolkrese.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Identities: Dance, Difference, and Self-fashioning

Abstract: In this article, we present two independent ethnographic studies-one examining belly dancing by white women in Central Ohio and one examining the salsa dance scene in the culturally diverse municipalities of Northern New Jersey-in order to complicate our understanding of how and why people draw upon traditions of cultural Others in their expressive behavior. We argue that dancers' accounts of their dancing experiences reveal these practices to be forms of self-fashioning aimed in part at liberating the dancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…These standards become institutionalized and constitute what is held to be creative, disqualifying from the outset expressions of creativity that do not meet them (Brandellero, 2011). Even when these standards are met, ethnic minority creatives and their work run a higher risk of being perceived and represented as 'other' and 'lesser', stressing their difference from the superior vantage point of a western subject and for his or her consumption (Bauman, 1977;Bock and Borland, 2011;Hutnyk, 2000;Kirshenblatt-Gimblett, 1998;Thoelen and Zanoni, 2016). A second mechanism of exclusion is rather related to the structurally disadvantaged position of minorities in social networks (Leslie et al, 2013).…”
Section: Ethnic Diversity In the Creative Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…These standards become institutionalized and constitute what is held to be creative, disqualifying from the outset expressions of creativity that do not meet them (Brandellero, 2011). Even when these standards are met, ethnic minority creatives and their work run a higher risk of being perceived and represented as 'other' and 'lesser', stressing their difference from the superior vantage point of a western subject and for his or her consumption (Bauman, 1977;Bock and Borland, 2011;Hutnyk, 2000;Kirshenblatt-Gimblett, 1998;Thoelen and Zanoni, 2016). A second mechanism of exclusion is rather related to the structurally disadvantaged position of minorities in social networks (Leslie et al, 2013).…”
Section: Ethnic Diversity In the Creative Industriesmentioning
confidence: 99%
“…Memories, biography, and experience are not randomly distributed, as they, to some degree, reflect one's position in the social world, including one's belonging to specific social groups. Yet creative products never automatically express collectively shared experience, in which case they rather come to be seen as folklore (Bauman, 1977;Bock and Borland, 2011). Creativity crucially needs a subject who processes those experiences, emotions, and ideas in a unique way to craft unique esthetic or semiotic content (Becker, 1982;Caves, 2000;Handke, 2004;Howkins, 2001;Scott, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Within the guise that most women practice it (leisure, exercise, and recreation; Moe, 2012), belly dance has been correlated with greater confidence, body acceptance, self-esteem, and happiness (Paul, 2006). It has also been associated with reducing stress and encouraging physical fitness, personal growth, and spirituality (Bock & Borland, 2011; Downey, Reel, SooHoo, & Zerbib, 2010; Kraus, 2010; Moe, 2011; Paul, 2006). Moreover, belly dance is often seen as an outlet for social support and community building (Moe, 2012, in press; Paul, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It has been argued that getting to know and training the body helps connect it to the mind (Kraus 2009). In addition, as indicated earlier, belly dance does not subscribe to the one narrow (thin and youthful) ideal, but is accepting of different physiques and the whole range of ages (Bock and Borland 2011). In Australia it is also typically practised in a female social environment, thus enabling a sense of connectedness between women.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in contrast to exotic dance, belly dance is accessible to women of all shapes and sizes. If anything, a fatter and curvier body type is valued as more suitable for belly dance's shimmies, rolls, and undulating movements (Bock and Borland 2011). As yet there exists little quantitative research on the body image of Australian or other belly dancers, but in their preliminary survey of U.S. belly dancers, Downey et al (2010) reported that the vast majority saw belly dance as a positive influence on their feelings about their body (and none cited it as a negative influence).…”
Section: Introductionmentioning
confidence: 99%